Elaboração de um espaço educador na Fundação Parque Zoológico de São Paulo para a conservação do mico-leão-preto (Leontopithecus chrysopygus) em uma perspectiva de educação ambiental crítica - Martins, Camila (Universidade Federal de São Carlos, 2015)
Wildlife conservation has been standing out on the world stage as one of the major issues of our time. Several institutions are mobilizing to develop effective strategies and actions to prevent the extinction of endangered species. Among these institutions, we remark the performance of zoos in the development of scientific research and educational activities, participation in endangered species programs, and promotion of entertainment for the visitors, thus compiling its four main attributions. In that sense, the São Paulo Zoo, besides performing its traditional role, including several educational activities, also participates and integrates endangered species conservation programs, such as the Black Lion Tamarin Conservation Program (Leontopithecus chrysopygus), conducting research about biology and ecology of populations from Floresta Nacional de Capão Bonito (Capão Bonito National Forest, São Paulo State). In this context, we developed in the present work a participatory educational process for planning and implementation of a space that educates at São Paulo Zoo about the black lion tamarin conservation. The research was conducted in a qualitative approach based on a participatory framework and using the participatory-actionresearch as a critical environmental education framework, intended to produce knowledge (research scope) to develop and implement a space that educates (action scope) from the participation of 23 professionals and 65 visitors (participation scope). In that sense, the research presents a procedural nature and was developed in four stages: Moment I - participatory diagnosis of the knowledge about the black lion tamarin from conducting individual interviews with São Paulo Zoo professionals and visitors; Moment II - two focal groups with the staff of the Zoo’s Education and Diffusion Division (DED) and Technical Team (ET) to elaborate the educational space proposal; Moment III: dialogue between the Zoo’s DED, ET, Engineering Division and Administrative Board for the space that educates implementation; Moment IV: reflexive analysis of the elaboration and implementation processes from focal groups with DED and ET, and participatory creation of manuals for the space. From the data obtained in the Moment I, it was possible to establish categories related to the structures and educational actions that would be implemented in the space that educates, which emerged from the dialogic process established between the participants and the researcher. Based on these categories, during the Moment II an educational proposal was developed containing the structural and educational features of the new space, consisting of four thematic kiosks, 23 panels, two educational games and a puppets theatre play about the species. In the Moment III, we observed a stronger participation of the São Paulo Zoo Technical Team at various stages of the implementation process, from the elaboration of visual and textual communication elements, to the building processes. In addition, as a consequence of this strengthening, the participants suggested and developed, in a participatory way, two manuals about the space aimed for environmental educators. Finally, during the Moment IV we observed that the use of participatory methodologies contributed to improve and strengthen the development of the space that educates, once the participants came to be regarded as subjects who share bonds to interpret the reality, and the dialogue established is linked to collective action in order to transform the socio-environmental problem in question, namely, the conservation of the black lion tamarin. We hope that the present research will contribute to the field of environmental education research in zoos and also to black lion tamarin conservation strategies, since it highlights the fact that it is possible to perform a participatory, reflective, cooperative and liberating practice.
Keywords: Zoológicos; Conservação da fauna; Metodologias participativas; Pesquisa-açãoparticipante; Educação ambiental crítica; Zoos; Wildlife conservation; Participatory methodologies; Participatory-Action- Research; CIENCIAS BIOLOGICAS::ZOOLOGIA::ZOOLOGIA APLICADA::CONSERVACAO DAS ESPECIES ANIMAIS